2018
DOI: 10.15766/mep_2374-8265.10691
|View full text |Cite
|
Sign up to set email alerts
|

A Neurology Clerkship Curriculum Using Video-Based Lectures and Just-in-Time Teaching (JiTT)

Abstract: Introduction: Just-in-time teaching is an educational strategy that involves tailoring in-session learning activities based on student performance in presession assessments. We implemented this strategy in a third-year neurology clerkship. Methods: Linked to core neurology clerkship lectures, eight brief videobased lectures and knowledge assessments were developed. Students watched videos and completed multiple-choice questions, and results were provided to faculty, who were given the opportunity to adjust the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…Comparison of student performance on knowledge-based questions between JiTT vs. non-JiTT courses from major assessments indicated that JiTT was helpful in student's learning of knowledge-based concepts. This is in agreement with previously reported observation that JiTT methodology effectively enhanced knowledge-based skills required for understanding of core health-care professional curricular topics (2,(6)(7)(8)(9)(10)15). Additionally, analysis of mean KR-20 values from each assessment also showed that courses with JiTT pedagogy had consistent exam performance compared to non-JiTT courses offered to the same cohorts.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Comparison of student performance on knowledge-based questions between JiTT vs. non-JiTT courses from major assessments indicated that JiTT was helpful in student's learning of knowledge-based concepts. This is in agreement with previously reported observation that JiTT methodology effectively enhanced knowledge-based skills required for understanding of core health-care professional curricular topics (2,(6)(7)(8)(9)(10)15). Additionally, analysis of mean KR-20 values from each assessment also showed that courses with JiTT pedagogy had consistent exam performance compared to non-JiTT courses offered to the same cohorts.…”
Section: Discussionsupporting
confidence: 91%
“…Results from assessment of JiTT approach implemented for biomechanics education indicated significantly higher learning gains and better understanding of a concept-based JiTT course, relative to a non-JiTT course (5). JiTT methodology effectively enhanced knowledge-based skills required for comprehensive understanding of topics including core health-care professional curricula (2,(6)(7)(8)(9)(10). Medical residency programs identified JiTT as an effective approach that helped residents in their interactive learning of clinical modules, increased learner participation during core sessions in the curriculum and enhanced retention of JiTT course content (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a review of the neurology education abstracts presented at the American Academy of Neurology (AAN) annual meetings from 2016–2019 (available at: https://issuu.com/americanacademyofneurology/docs), only 2 focused on the flipped classroom format, which was used to deliver content for a specific subject within the curriculum. Similarly, explorations of neurology education resources on the MedEdPORTAL (available at: https://www.mededportal.org/) resulted in 0 of the 44 resources fitting the description of a flipped classroom; however, there is one report from Yale that describes modification of the classroom lecture based on a preclass assessment taken by the students . Overall, there is a relative dearth of reports from the medical literature regarding implementing flipped classrooms in neurology education, which flags a methodological gap that our field needs to explore further.…”
Section: Current Implementations In Neurologymentioning
confidence: 99%
“…Similarly, explorations of neurology education resources on the MedEdPORTAL (available at: https://www.mededportal.org/) resulted in 0 of the 44 resources fitting the description of a flipped classroom; however, there is one report from Yale that describes modification of the classroom lecture based on a preclass assessment taken by the students. 26 Overall, there is a relative dearth of reports from the medical literature regarding implementing flipped classrooms in neurology education, which flags a methodological gap that our field needs to explore further.…”
Section: Current Implementations In Neurologymentioning
confidence: 99%